2016
DOI: 10.1021/acs.est.5b05965
|View full text |Cite
|
Sign up to set email alerts
|

Two Centuries of Coral Skeletons from the Northern South China Sea Record Mercury Emissions from Modern Chinese Wars

Abstract: The contemporary mercury (Hg) cycle in the world's oceans has been greatly affected by human activities. However, we are still lacking reliable, long-term, and continuous records of Hg in seawater. Here, we report for the first time on using annually banded Porites coral skeletons from the northern South China Sea (SCS) as an archive for recording changes of seawater dissolved Hg spanning the past two centuries. We developed a combustion-trapping method to preconcentrate ultratrace Hg concentrations from coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Elevated levels of Hg in fish near munitions dumpsites have been attributed to mercury fulminate (Della Torre et al, 2010), although a definitive link was not shown. Mercury records in corals from the South China Sea show peaks in concentration that appear to coincide with regional wars (Sun et al, 2016). However, it is unclear if a munition Hg source is substantial enough to sufficiently elevate concentrations in seawater (C. Lamborg, as cited by Monahan, 2016).…”
Section: Metalsmentioning
confidence: 99%
“…Elevated levels of Hg in fish near munitions dumpsites have been attributed to mercury fulminate (Della Torre et al, 2010), although a definitive link was not shown. Mercury records in corals from the South China Sea show peaks in concentration that appear to coincide with regional wars (Sun et al, 2016). However, it is unclear if a munition Hg source is substantial enough to sufficiently elevate concentrations in seawater (C. Lamborg, as cited by Monahan, 2016).…”
Section: Metalsmentioning
confidence: 99%
“…Several sites in remote regions from South and North America have also shown high Hg accumulation rates around CE 1940 (Beal et al, 2015;Biester et al, 2002;Schuster et al, 2002). Coral skeletons from the South China Sea and North Atlantic myctophids, have also revealed the highest Hg concentrations in the marine realm during the WWII (Martins et al, 2006;Sun et al, 2016). This global increase in Hg deposition highlights the long-range atmospheric transport of gaseous Hg, from anthropogenic emission sources to remote areas where atmospheric Hg can be oxidized to divalent Hg (Hg II ), and deposited onto terrestrial and marine ecosystems (Wang et al, 2014).…”
Section: Industrial Period (Ce 1840-present)mentioning
confidence: 99%
“…As reported by R. Sun et al. (2016), coral skeletons from the northern South China Sea have recorded significant Hg emissions from modern Chinese wars during the period of 1800–2000. Unraveling the input pathway, transformation, and fate of these historically anthropogenic Hg in the coastal environment is thus a challenging but imperative task.…”
Section: Introductionmentioning
confidence: 64%